2021
DOI: 10.3389/fcell.2021.757184
|View full text |Cite|
|
Sign up to set email alerts
|

Increased ATG5 Expression Predicts Poor Prognosis and Promotes EMT in Cervical Carcinoma

Abstract: Cervical cancer has the second-highest incidence and mortality of female malignancy. The major causes of mortality in patients with cervical cancer are invasion and metastasis. The epithelial–mesenchymal transition (EMT) process plays a major role in the acquisition of metastatic potential and motility. Autophagy-related genes (ARGs) are implicated in the EMT process, and autophagy exerts a dual function in EMT management at different phases of tumor progression. However, the role of specific ARGs during the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…EMT has been identified as a critical driver of embryonic development, tissue fibrosis, wound healing, tumorigenesis, and metastasis 12,32 . As previously described by many studies, patients with enriched EMT‐related gene expression are associated with a poorer prognosis in many human cancers 33–35 . In our study, the high‐risk group we identified also has the characteristics of EMT signal pathway activation and a worse prognosis, which is consistent with the previous study (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…EMT has been identified as a critical driver of embryonic development, tissue fibrosis, wound healing, tumorigenesis, and metastasis 12,32 . As previously described by many studies, patients with enriched EMT‐related gene expression are associated with a poorer prognosis in many human cancers 33–35 . In our study, the high‐risk group we identified also has the characteristics of EMT signal pathway activation and a worse prognosis, which is consistent with the previous study (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 92%
“… 12 , 32 As previously described by many studies, patients with enriched EMT‐related gene expression are associated with a poorer prognosis in many human cancers. 33 , 34 , 35 In our study, the high‐risk group we identified also has the characteristics of EMT signal pathway activation and a worse prognosis, which is consistent with the previous study (Figures 3 and 4 ). A mesenchymal subtype of GC (defined by a positive EMT signature) often showed increasing resistance to radio‐ and chemotherapeutics and poor response to ICB treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Further evidence has suggested that autophagy plays a fundamental role in the EMT in cancer [ 18 ]. Given the complex relationship between the two processes, we examined the influence of autophagy on EMT in HLE cells through two specific autophagy modulators, rapa and 3-MA.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the tumors activate the epithelial-mesenchymal transition (EMT) program to attain the stem cell-like properties and to promote their growth, invasion, and metastasis. The autophagy-related genes, especially ATG5 play a critical role in the EMT process as indicated by a study on cervical cancer cells ( 119 ). In radio-resistant cancer cells, like pancreatic ductal adenocarcinoma cells and NSCLC stem cells, autophagy has found to be essential in promoting tumor growth and invasiveness ( 120 ) as well as maintaining the stem cell-like properties ( 121 ) of the cells.…”
Section: Influence Of Autophagy On Radiation Response Of Tumorsmentioning
confidence: 99%